Analysis of Meenachil watershed using foss GIS tools - RAHUL B. T; Sumit Kumar Jha; Er. Vishnu B (Guide) (Tavanur 2012 Department of Land and Water Resource Conservation engineering)
Analysis of Meenachil watershed using foss GIS tools
Analysis of Meenachil watershed using foss GIS tools